Use of microalgae as a biofilm in biophotovoltaic panels: a bibliometric analysis - Patrocinio Gomes, Vanielle Aparecida; Passos, Caroline Tedesco Santos; Leite, Luisa Alves; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2020)
Traditional energy sources are beginning to make room for renewable sources with less greenhouse gas emissions. These include solar energy, which does not have a better cost-benefit ratio, even with the price of solar panels falling sharply, being considered expensive in relation to other renewable sources. For this reason, research intensifies in the search to reduce these productive costs, such as a new generation of solar cells, using biological photovoltaic devices - BPV. Thus, this study brings a bibliometric analysis, with the objective of gathering existing data in the literature on the subject. As a result, it is observed that it is a really current and promising topic and studies on biophotovoltaic panels are concentrated in England and Malaysia, with researchers from these countries working together, that is, the research group is restricted and covers only researchers from the same research circle.